2014
DOI: 10.1177/0886260514553113
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Among Bullying, Homophobic Teasing, and Sexual Violence Perpetration Among Middle School Students

Abstract: Bullying perpetration and sexual harassment perpetration among adolescents are major public health issues. However, few studies have addressed the empirical link between being a perpetrator of bullying and subsequent sexual harassment perpetration among early adolescents in the literature. Homophobic teasing has been shown to be common among middle school youth and was tested as a moderator of the link between bullying and sexual harassment perpetration in this 2-year longitudinal study. More specifically, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
100
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 46 publications
(79 reference statements)
13
100
0
10
Order By: Relevance
“…These associations have been supported with the Bully-Sexual Violence Pathway theory (Espelage et al 2012) supported by Espelage et al (2015a), who found that bullying perpetration was a predictor of sexual violence perpetration over a two-year middle school longitudinal study. Further, the association between bullying and sexual violence was moderated by homophobic name-calling perpetration among males; the link between bullying and sexual violence for males was strongest among students who reported directing homophobic epithets at other students.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…These associations have been supported with the Bully-Sexual Violence Pathway theory (Espelage et al 2012) supported by Espelage et al (2015a), who found that bullying perpetration was a predictor of sexual violence perpetration over a two-year middle school longitudinal study. Further, the association between bullying and sexual violence was moderated by homophobic name-calling perpetration among males; the link between bullying and sexual violence for males was strongest among students who reported directing homophobic epithets at other students.…”
Section: Introductionmentioning
confidence: 73%
“…Bullying, homophobic name-calling, and sexual violence perpetration emerge during early adolescence and appear to be associated with one another both in cross-sectional and longitudinal studies (Espelage et al 2015a; Espelage et al 2012). These associations have been supported with the Bully-Sexual Violence Pathway theory (Espelage et al 2012) supported by Espelage et al (2015a), who found that bullying perpetration was a predictor of sexual violence perpetration over a two-year middle school longitudinal study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…About half of the students in 7th through 12th grades were the victims of sexual harassment at school during the 2010-11 school year, with 56% of females and 40% of males experiencing sexual harassment in person or online (AAUW, 2011). Further, in a middle school study including over 1200 students, 20% of females and 34% of males reported directing homophobic epithets toward other peers in the last month (Espelage, Basile, & Hamburger, 2014). As most of the programming for the prevention of sexual violence is directed at high school and college samples, this study addresses a significant gap in the growing body of prevention science focused on reducing sexual violence among middle school youth.…”
Section: Discussionmentioning
confidence: 96%
“…This may also be interpreted as associates to the oppressive social circumscriptions of non-heteronormative behavior ( 2014), which increases significantly the chances for social exclusion and traumatic life events, such as physical and emotional abuse and neglect (Espelage et al, 2014), as well as higher rates of suicidal ideation and attempts (Teixeira-Filho and Rondini, 2012). In fact, the emotional and affective profile outlined in this study resembles the one delineated in an investigation of temperament traits and affective types associated with childhood abuse and neglect experiences (Sudbrack et al, 2015).…”
Section: Discussionmentioning
confidence: 98%